2023
DOI: 10.3390/polym15061552
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Mechanical Properties of Polymer Composites with Hexagonal Boron Nitride—A Comparison of Three Processing Methods: Injection Moulding, Powder Bed Fusion and Casting

Abstract: Materials providing heat dissipation and electrical insulation are required for many electronic and medical devices. Polymer composites with hexagonal boron nitride (hBN) may fulfil such requirements. The focus of this study is to compare composites with hBN fabricated by injection moulding (IM), powder bed fusion (PBF) and casting. The specimens were characterised by measuring thermal conductivity, tensile properties, hardness and hBN particle orientation. A thermoplastic polyurethane (TPU) was selected as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…This study is a continuation of our previous research on the encapsulation of interventional medical devices [33] and thermally conductive polymer composites [35]. This paper adds results for composites with different hBN powder types, and how the hBN platelets' orientation in the injection moulding process can be simulated.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…This study is a continuation of our previous research on the encapsulation of interventional medical devices [33] and thermally conductive polymer composites [35]. This paper adds results for composites with different hBN powder types, and how the hBN platelets' orientation in the injection moulding process can be simulated.…”
Section: Introductionmentioning
confidence: 85%
“…In our previous work [35] we showed that injection moulding induces a preferred orientation of the platelets, with the platelet normal along the thickness direction of the specimens. The orientation varied through the thickness of the moulded specimens, and it increased with increasing hBN loading.…”
Section: B Anisotropy Of Thermal Conductivitymentioning
confidence: 93%
See 3 more Smart Citations